LANDSLIDE VULNERABILITY ZONE MODELING BASED ON AHP-GIS AND GEOELECTRIC METHOD VERIFICATION: AN EARLY DETECTION STRATEGY IN SEBULU DISTRICT, KUTAI KARTANEGARA REGENCY - Fadillah, Rizky; Djayus, Djayus; Khoirunisa, Nanda (Department of Geodesy Engineering, Faculty of Engineering, Diponegoro University,Indonesia, 2025)
Landslides and soil movement frequently occur in Sebulu District, especially on the main access road. This study aims to analyze the vulnerability to landslides in Sebulu District, Kutai Kartanegara Regency, using the Analytical Hierarchy Process (AHP) and Geographic Information System (GIS) approaches, with verification through the geoelectric method. The advantage of this integrated approach is its ability to combine multi-criteria spatial modeling with physical validation of subsurface conditions, thereby producing a more comprehensive and reliable analysis. The secondary data used includes geological information, rainfall, slope gradient, soil type, and land cover. By applying AHP weighting, landslide vulnerability values were obtained with